Edukasi Kesehatan Pencegahan Penyebaran HIV/AIDS pada Anak Didik Pemasyarakatan (ANDIKPAS LPKA) di Sungai Raya, Kalimantan Barat - Fitri Fujiana; Herman Herman; Triyana Harlia Putri; Virgilius Phasacola Tiko Kafaso; Nadya Eulalia; Tamara Septia Chairunisa (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The risk of HIV/AIDS transmission increases for children in juvenile prisons. This is due to the association of prison children close to factors that trigger transmissions, such as a history of drug use and risky sexual behaviour. Lack of information and education related to HIV/AIDS makes andikpas less concerned about taking care of themselves to avoid transmission of HIV/AIDS. Transmission and prevention of the spread of HIV/AIDS can be done through Health Education. This activity aims to increase understanding of HIV/AIDS for correctional students (ANDIKPAS) at LPKA Sungai Raya, West Kalimantan Province. This activity took place offline on 7 September 2022, involving 23 participants. The results of this activity showed an increase in the knowledge score after being given the intervention. This increase in knowledge is expected to improve the behaviour of LPKA Sungai Raya children in carrying out HIV-AIDS prevention. For the next activity, it is recommended to carry out educational activities as well as VCT screening examinations for LPKA Sungai Raya children so that they can provide first aid as soon as possible for those positively improve prevention for those with negative results.